Bidding Rings and the Winner's Curse: The Case of Federal Offshore Oil and Gas Lease Auctions - Ken Hendricks; Robert H. Porter; Guofu Tan (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2003)
This paper extends the theory of legal cartels to a.liated private value and common value environments, and applies the theory to explain joint bidding patterns in U.S. federal government o.shore oil and gas lease auctions. We show that e.cient collusion is always possible in private value environments, but may not be in common value environments. In the latter case, fear of the winner's curse can cause bidders not to bid, which leads to ine.cient trade. Buyers with high signals may be better o. if no one colludes. The bid data is consistent with oil and gas leases being common value assets, and with the prediction that the winner's curse can prevent rings from forming on marginal tracts.
Keywords: 330; Kartell; Auktion; Erdölkonzession; USA